The Influence of Financial Technology (Fintech) Development on The Financial Performance of Conventional Banks - Dhita Amalia Putri; Eskasari Putri (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the influence of financial technology (fintech) development on the financial performance of conventional banks in Indonesia. Employing a quantitative approach, secondary data were collected from financial reports, official websites, and documentation of banks listed on the Indonesia Stock Exchange (IDX) during 2020–2022. The sample included banks with publicly available financial data on Internet Banking, Mobile Banking, and SMS Banking. Descriptive statistics summarize the financial performance and digital banking services, while classical assumption tests ensure the suitability of multiple linear regression for hypothesis testing. The study analyzes the effects of Internet Banking, Mobile Banking, SMS Banking, Capital Adequacy Ratio (CAR), Operating Expenses to Operating Income (BOPO), and firm size on financial performance, measured by Return on Assets (ROA) and Return on Equity (ROE). The results indicate that Internet Banking, Mobile Banking, and SMS Banking do not significantly affect ROA or ROE, with significance values ranging from 0.463 to 0.898. This limited impact is attributed to high technology costs, suboptimal utilization, evolving customer preferences, and the restricted functionality of SMS Banking. The findings suggest that banks need to optimize digital banking services and consider additional fintech innovations to enhance financial performance.